(untitled) (Research, Society and Development, 2023)
To investigate through bibliometric parameters the blood cell changes in patients infected with the SARS-CoV-2 virus, described in the literature in 2020. This study used the bibliometric parameters to carry out the research with the creation of a search key to carry out the selection of articles and, through this, analyze the scientific findings quantitatively. The selection of articles was performed in May 2022, without language and year of publication restrictions, in the Web of Science database (Clarivate Analytics, Philadelphia, PA, USA). The search strategy retrieved 26,896 articles in the cited database. A total of 678 articles were evaluated, and only 17 articles had the searched endpoint. The most cited article was: "Dysregulation of Immune Response in Patients with Coronavirus 2019 (COVID-19) in Wuhan, China", published in the journal Clinical Infectious Diseases. More than 70% of the studies were conducted in China and 100% of them exposed changes in platelet and/or white blood cell parameters. Despite the low rate of selected articles and the need for more robust studies on this topic, we have noticed increasing rates of citations, renowned institutions, and scholars researching on the subject as well as in other countries besides China. Thus, this study developed some indicators to assist in future research on the subject.